2007
DOI: 10.1021/jp071783e
|View full text |Cite
|
Sign up to set email alerts
|

Strong Bonding of Single C60 Molecules to (1 × 2)-Pt(110):  an STM/DFT Investigation

Abstract: The interaction of single C 60 molecules with the (1 × 2)-Pt(110) surface has been studied by scanning tunneling microscopy and density functional theory (DFT) calculations on slab models. Molecules are observed to be frozen at room temperature and are found to be almost exclusively in the same configuration. Extensive DFT calculations show that this configuration is the global energy minimum, suggesting that adsorbed molecules have enough rototranslational freedom to escape from the numerous local minima. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(41 citation statements)
references
References 34 publications
4
37
0
Order By: Relevance
“…5͑b͒ can also be compared to highresolution STM images and corresponding densityfunctional-theory ͑DFT͒ simulations of C 60 on a Pt͑110͒ surface in Fig. 10͑A͒ of Casarin et al 15 The geometry of Casarin et al's results is not quite the same as ours with a hexagon rotated slightly from the center of the image ͑an orientation which these authors call M1, as shown in their Fig. 3͒.…”
Section: Orbital Pictures and Stm Simulationsmentioning
confidence: 79%
See 1 more Smart Citation
“…5͑b͒ can also be compared to highresolution STM images and corresponding densityfunctional-theory ͑DFT͒ simulations of C 60 on a Pt͑110͒ surface in Fig. 10͑A͒ of Casarin et al 15 The geometry of Casarin et al's results is not quite the same as ours with a hexagon rotated slightly from the center of the image ͑an orientation which these authors call M1, as shown in their Fig. 3͒.…”
Section: Orbital Pictures and Stm Simulationsmentioning
confidence: 79%
“…7 Single C 60 molecules on a Pt͑111͒ surface are found to reside in a fourfold site. 15 In this paper, we will consider the case where C 60 is subject to a local field of C 6v symmetry, as this is the highest of the allowed symmetries. However, extension to sites of lower symmetry is readily accomplished if required.…”
Section: B Surface Interactionsmentioning
confidence: 99%
“…On the other hand, it has been well established in numerous combined STM and DFT studies on individual and monolayer C 60 how the intramolecular resolution relates to the azimuthal orientation of the molecules on a variety of different surfaces, 6,8,11,[32][33][34][35][36][37][38] and so this aspect of the molecular bonding can be readily obtained.…”
Section: Introductionmentioning
confidence: 99%
“…The problem of charge transfer from metals to C 60 molecules adsorbed on their surfaces has been addressed by several authors using both experimental [16,17,18,19] and theoretical approaches [15,20,21]. A (non-exhaustive) summary of their results is given in Table 1, which also lists the work functions of the substrates involved.…”
Section: Charge Transfermentioning
confidence: 99%